The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1517/13543784.8.10.1683
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine improves glycaemic control and serum lipid profile in obese Type 2 diabetic subjects: a new approach in the treatment of diabetes

Abstract: Bromocriptine, a potent dopamine D(2) receptor agonist, has been shown to reduce insulin resistance, glucose intolerance and hyperlipidaemia in both numerous animal studies and in Phase II studies. Bromocriptine has been used worldwide for over 20 years to treat Parkinson's disease, macroprolactinoma and other disorders; it has been found to be generally safe. We therefore investigated the possible beneficial effects of Ergoset(R) (Ergo Science Corp.), a new quick release formulation of bromocriptine, on glyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 88 publications
2
115
1
6
Order By: Relevance
“…Bromocriptine-QR therapy reduced mean postprandial glucose levels from 135 ± 5 mg/dl to 117 ± 3 mg/dl (P < 0.05) and fasting and postprandial plasma insulin levels from 27 ± 6 μU/ml and 99 ± 13 μU/ml to 15 ± 2 μU/ml and 50 ± 7 μU/ml, respectively (P < 0.05) (Figure 7). The above study of bromocriptine-QR impact on mealtime glucose and insulin was reconducted in T2DM subjects naïve to any anti-diabetes drug treatment [161,162]. Average study population baseline demographics included a percent-glycated HbA1c of 8.9, BMI of 31.5, duration of diabetes of 3.9 years (however, the study was conducted at a time when a fasting glucose level of 140 mg/dl was used as a diagnosis of T2DM so dysglycemia likely was present for a longer period of time), and age of 55 years.…”
Section: Clinical Effects Of Bromocriptine-qr Therapy In the Treatmenmentioning
confidence: 99%
See 2 more Smart Citations
“…Bromocriptine-QR therapy reduced mean postprandial glucose levels from 135 ± 5 mg/dl to 117 ± 3 mg/dl (P < 0.05) and fasting and postprandial plasma insulin levels from 27 ± 6 μU/ml and 99 ± 13 μU/ml to 15 ± 2 μU/ml and 50 ± 7 μU/ml, respectively (P < 0.05) (Figure 7). The above study of bromocriptine-QR impact on mealtime glucose and insulin was reconducted in T2DM subjects naïve to any anti-diabetes drug treatment [161,162]. Average study population baseline demographics included a percent-glycated HbA1c of 8.9, BMI of 31.5, duration of diabetes of 3.9 years (however, the study was conducted at a time when a fasting glucose level of 140 mg/dl was used as a diagnosis of T2DM so dysglycemia likely was present for a longer period of time), and age of 55 years.…”
Section: Clinical Effects Of Bromocriptine-qr Therapy In the Treatmenmentioning
confidence: 99%
“…Subsequent clinical studies investigated the possible beneficial effects of bromocriptine-QR on glycemic control in obese T2DM subjects whose dysglycemia was poorly controlled on SU and/or metformin therapies. One such study investigated the impact of morning administration (8 a.m.) of bromocriptine-QR (1.6-4.8 mg/day; titrated up at a rate of 0.8 mg/week until a maximum tolerated dose of 1.6-4.8 mg/day was achieved) or placebo upon glycemic control in obese T2DM subjects very poorly controlled on baseline SU therapy (485 subjects) while held on a weight maintaining diet for 24 weeks (the SU add-on study) [161]. Average population baseline demographics included a percent-glycated HbA1c level of 9.4, BMI of 32.1, duration of disease of 6.3 years (the study was conducted at a time when a fasting glucose level of 140 mg/dl was used as a diagnosis of T2DM so dysglycemia likely was present for a longer period of time) and age of 55 years.…”
Section: Clinical Effects Of Bromocriptine-qr Therapy In the Treatmenmentioning
confidence: 99%
See 1 more Smart Citation
“…However in these studies, fasting plasma glucose reductions in response to such treatment varied from not at all to moderate depending upon the prevailing glucose level. In Type 2 Diabetes Mellitus (T2DM) subjects, such once daily (morning) treatment with bromocriptine-QR, a Food and Drug Administration (FDA) approved quick release formulation of bromocriptine for the treatment of T2DM, reduced postprandial glucose across the three meals of the day and, these postprandial glucose reductions were larger than those observed in the pre-prandial (intermeal) state [5,6]. Collectively these findings suggest that the plasma glucose disposal/glucose homeostasis effects of timed bromocriptine administration may be more potent during the postprandial versus fasting state and that such bromocriptine treatment may potentially act as a unique postprandial "weighted" insulin sensitizer.…”
Section: Introductionmentioning
confidence: 99%
“…[21] A 24 weeks randomized controlled trial by Cincotta et al in 1999 showed a significant reduction in plasma free fatty acids and triglycerides after administration of bromocriptine mesylate in obese T2DM patients. [22] …”
Section: Bromocriptine and Lipid Profilementioning
confidence: 99%